Accommodative-Hybrid Religious Encounters and Interfaith Dialogue: A Study of Lamaholot Muslims and Catholics in East Flores - Anselmus Dorewoho Atasoge; Fatimah Husein; Siswanto Masruri (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
This paper focused its attention on three main problems. First, the changes occurred when ancestral religious rituals in Lamaholot collided with Islam and Catholicism. Second, the social cohesion capital possessed by the Lamaholot community in building interreligious and interfaith dialogue in East Flores. Third, the challenges faced, and negotiations carried out in the interreligious and interfaith interaction and dialogue. This paper is constructed upon structural functionalism theory. Data was collected using observations, interviews, and documents. Data analysis method and technique used in this paper were interpretive qualitative. This paper identified two domains as entry points for developing interreligious and interfaith dialogue. First, the concepts of divinity in local Lamaholot rituals and in the world’s religions (Islam and Catholicism) meet and strengthen each other and become the epistemological basis for dialogue. Second, Lamaholot rituals become a medium for transmitting the values of Lamaholot solidarity.